2019
DOI: 10.1038/s41598-019-43080-2
|View full text |Cite
|
Sign up to set email alerts
|

CRISPR/Cas9-mediated generation of a tyrosine hydroxylase reporter iPSC line for live imaging and isolation of dopaminergic neurons

Abstract: Patient-specific induced pluripotent stem cells (iPSCs) are a powerful tool to investigate the molecular mechanisms underlying Parkinson’s disease (PD), and might provide novel platforms for systematic drug screening. Several strategies have been developed to generate iPSC-derived tyrosine hydroxylase (TH)-positive dopaminergic neurons (DAn), the clinically relevant cell type in PD; however, they often result in mixed neuronal cultures containing only a small proportion of TH-positive DAn. To overcome this lim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
29
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(29 citation statements)
references
References 24 publications
0
29
0
Order By: Relevance
“…In the present study, we first established TH-GFP iPSC lines from not only controls but also a patient with a PRKN mutation and first analyzed these cells using live cell imaging and CLEM to evaluate the structure and function of mitochondria specifically in dopaminergic neurons. Several studies have reported the establishment of TH reporter iPSC lines using gene editing technology for transcriptome profiling or the electrical properties of dopaminergic neurons [ 23 25 ]. Immunohistochemistry confirmed that the specificity of our TH-GFP iPSC lines was sufficient for the identification of dopaminergic neurons, similar to that of other knock-in reporters using genome editing technology.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the present study, we first established TH-GFP iPSC lines from not only controls but also a patient with a PRKN mutation and first analyzed these cells using live cell imaging and CLEM to evaluate the structure and function of mitochondria specifically in dopaminergic neurons. Several studies have reported the establishment of TH reporter iPSC lines using gene editing technology for transcriptome profiling or the electrical properties of dopaminergic neurons [ 23 25 ]. Immunohistochemistry confirmed that the specificity of our TH-GFP iPSC lines was sufficient for the identification of dopaminergic neurons, similar to that of other knock-in reporters using genome editing technology.…”
Section: Discussionmentioning
confidence: 99%
“…It is therefore necessary to selectively label dopaminergic neurons among the mixture of dopaminergic and non-dopaminergic neurons that are derived from iPSCs. Recently, several studies have reported the successful purification of dopaminergic neurons carrying a tyrosine hydroxylase (TH; a marker for identifying dopaminergic neurons) knock-in reporter, either using the genome editing technology TALEN (transcription activator-like effector nuclease) or CRISPR/Cas9 systems [ 23 25 ]. However, the generation of TH reporter iPSC lines derived from PD patients, including those with PRKN mutations, has not been reported.…”
Section: Introductionmentioning
confidence: 99%
“…The use of reporter gene that is selectively expressed in post-mitotic DA neurons is a convenient solution to detect these cells in heterogenous cultures. Thus, reporter iPS cell lines expressing GFP [ 87 , 88 ] or the brighter reporter protein mOrange [ 89 ] under the control of TH promoter were developed using the CRISPR Cas9 genome editing system. These genetic modifications facilitated the identification of DA neurons in mixed neuron cultures and xenotransplants, and even enabled their isolation in a viable state by FACS [ 89 ].…”
Section: Directed Differentiation Of Es and Ips Cells Into The Midmentioning
confidence: 99%
“…Generation of tagged-parvalbumin neurons by a CRISPR/Cas9 approach as a tool to follow PVALB neuron cell fate The CRISPR/Cas9 genome-editing technology (reviewed in [53]) has been broadly used to modify iPSC and recently, many studies successfully demonstrated the generation of human iPSC lines expressing a fluorescent protein that faithfully recapitulates the endogenous expression of a given protein [54,55]. Through a CRISPR/Cas9 approach, one could insert a reporter cassette (i.e., eGFP, tdTomato), whose expression is driven by the endogenous PVALB promoter, allowing to follow the fate of these neurons once PV expression starts.…”
Section: Asd Ipsc and Parvalbumin Interneuronsmentioning
confidence: 99%